Minutes of 14th technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 14th Technical and Progress Monitoring (TPM) meeting (session lI) of BRACU new campus, held on 16th April, 2019.